Bohemian rulers of the Luxembourg dynasty and the Poděbrady family in the medieval Silesian and Kłodzko chronicles of canons regulars in Kłodzko, Wrocław and Żagań - Chmielewska, Katarzyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
The author based on three monastery chronicles of the Late Middle Ages analyses the method of portraying the Bohemian kings from the Luxembourg and Poděbrady families and tries to point out factors which influenced this method of chronicle narration. The sources for this article are canons’ regulars chronicles in Żagań, Wrocław and Kłodzko: Catalogus abbatum Saganensium, Chronica abbatum Beatae Mariae Virginis in Arena i Cronica Monasterii Canonicorum Regularium in Glacz. The figures of rulers appear in the chronicles mainly in the context of their relationships with the particular monastery, especially when it comes to property matters: granting, rights and taxes. The other aspect in which the rulers are mentioned in the chronicles are the conflicts between secular and Church power. From the analysis of the texts a conclusion can be drawn that the picture of the rulers is diverse in different places where the chronicles were written and the attitude of the local society towards the particular ruler. It is best seen on the example of George of Poděbrady, a Hussite on the Bohemian throne. The chronicle of Żagań has a separate position – apart from the local issues, it presents the general information, unrelated to Church, including the ruling persons.

Autorka na podstawie trzech kronik klasztornych powstałych w późnym średniowieczu analizuje sposób przedstawienia czeskich królów z dynastii Luksemburgów i Podiebradów oraz stara się wskazać przyczyny, które wpłynęły na taki właśnie tok narracji kronikarskiej. Podstawę źródłową tych rozważań stanowią kroniki spisane w klasztorach kanoników regularnych reguły św. Augustyna w Żaganiu, Wrocławiu i Kłodzku: Catalogus abbatum Saganensium, Chronica abbatum Beatae Mariae Virginis in Arena i Cronica Monasterii Canonicorum Regularium in Glacz. Postacie władców pojawiają się w tych źródłach przede wszystkim w kontekście ich związków z konkretnym klasztorem, szczególnie w sprawach majątkowych dotyczących nadań, praw własności i podatków. Królowie czescy wspominani są też na kartach kronik przy okazji opisów konfliktów między władzą świecką a kościelną. Z analizy tekstu dzieł wynika, że obraz panujących jest zróżnicowany, zależny od miejsca powstania kroniki i stosunku lokalnej społeczności do konkretnego władcy. Najlepiej uwidacznia się to na przykładzie Jerzego z Podiebradu, husyty na tronie czeskim. Osobne miejsce w tym zestawieniu zajmuje kronika żagańska przedstawiająca oprócz zagadnień lokalnych także informacje o ogólnym ponadklasztornym charakterze, w tym informacje o osobach panujących.
Keywords: canons regulars; monastery chronicles; historiography; the Middle Ages; Bohemian rulers; kanonicy regularni; kroniki klasztorne; dziejopisarstwo; średniowiecze; czescy władcy